Voices Within: How NCII Survivors Reconstruct Self Concept Through Intrapersonal Communication - Devinia, Keisha Aurellia; Arifputri, Aiza Nabilla (JURNAL KOMUNIKASI INDONESIA, 2026)
This study examines Non-Consensual Intimate Image Sharing (NCII) as a form of digital gender-based violence that disrupts women’s self-concept beyond its psychological consequences, particularly among female victims active on social media. It aims to analyze their intrapersonal communication experiences and how they redefine self-concept following the incident. This study employs a qualitative approach, gathering data by performing in-depth interview with five female NCII victims who actively use social media platforms, such as Instagram, Facebook, TikTok, Telegram, and X. The study draws on Stuart & Laraia’s (1998) self-concept theory, which includes five analytical dimensions: body image, ideal self, self-esteem, role performance, and personal identity. This strategy was chosen to explore the lived experiences and personal interpretations of each informant. The findings reveal that intrapersonal communication plays a crucial role in helping the victims process trauma, evaluate self-worth, and reconstruct a positive self-image. Although each informant demonstrated different coping mechanisms, intrapersonal communication emerged as an important tool in the healing process and in reconstructing their self-perception. These findings underscore the need for a more comprehensive recovery approach that considers psychological and social aspects in supporting NCII victims.